(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The Barremian succession in the present study is represented by the Zubair Formation which is the most significant sandstone reservoir in Iraq. The area of study is located in the Southern part of Iraq at the Luhais and Rachi oil fields, within the Mesopotamian basin. The petrographic study showed that quartz mineral is the main component of the sandstone in Zubair Formation with minor percentage of feldspar and rare rock fragments to be classified as quartz arenite. There are five lithologic changes (lithofacies) that are characterized the studied succession: - course to medium sandstone well sorted, fine sandstone well sorted, course to medium sand poorly sorted, clay sandstone poorly sorted, and shale. These lithofacieses were deposited in the deltaic environments as three associated facies [delta plane, delta front and lacustrine (marsh)]. The main diagenetic processes affected Zubair Formation in different intensity are cementation, compaction, dissolution, and dolomitization these processes affected porosity in different ways and stages. The different lithofacies contributed to division of the Zubair Formation into three distinct rock units, which were used in interpreting and distributing the suggested environments. The lower unit is composed of shale with lenses of fine sand with high organic matter, and it was deposited in the flood-delta plain environment. The presence of the delta plain associated facies overlaying the unconformity surface (SB1) referred to the transgressive system tract (TST). This stage has ended with a channel fills deposit to mark a high-stand system tract (HST). The middle unit is composed of sandstone with the shale inter layers with high amount of heavy minerals, which was deposited in the distributary-mouth-bar within the delta front environment. There are two sequences as TST in this part, which ends with the maximum sea level rise (mfs) to mark the upper part of the Zubair Formation. While the upper part is composed of shale with high amount of pyrite and organic matters. This represents the lacustrine (marsh) associated facies within the delta plain environment, which deposited during the high stand stage. The sea level rise marks the end of this stage with the deposition the upper part of Zubair Formation, and the beginning of deposition of the Shuaiba Formation as shallow carbonate marine.